The influence of ethical leadership practices on employees' perception of distributive equity at HYPROC SC - Boutiba, Mokhtaria; Meliani, Khaled (The International tax journal, 2025)
With the growing number of business scandals, corporate misconduct, bribery, and fraudulent accounting practices that endure making headlines, ethical leadership is emerging as a powerful catalyst for establishing a sustainable organizational culture. It is not simply a moral inspiration, but a strategic necessity for building prosperous staff and companies in the long term. Distributive equity is the most important component in fostering employees’ contentedness, commitment and loyalty to the company. This study investigates whether HYPROC SC practices, in the context of ethical leadership, affect distributive equity. The researchers wield a questionnaire administered to the employees of the HYPROC Company. Data collection and analysis were performed using SPSS V26 software. The reliability of the model was tested, and the research hypothesis was verified using the Smart PLS V4 software. Despite the positive perception of ethical leadership, the findings indicate that it does not significantly influence employees’ sense of distributive equity. This suggests that ethical leadership alone may be insufficient to ensure perceived fairness in the workplace. The study underscores the importance of integrating ethical leadership with transparent and equitable human resource practices to enhance employee satisfaction, commitment, and long-term organizational performance.